ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN SISTEM INFORMASI AKUNTANSI PADA PT. KARYA SEMANGAT MANDIRI (KSM) - Sartika, Wanda Ayu; Harahap, Wilda Sri Munawaroh (Al-Buhuts, 2023)
This study aims to determine the Analysis of Factors Influencing Interest in Utilizing Accounting Information Systems at PT. Karya Mandiri Spirit (KSM) In this study, the authors used a descriptive and quantitative research approach with the type of associative research, because there are variables to be examined and the relationship is intended to present an overview of the relationships between the variables studied. The population in this study are all employees at PT. Mandiri Spirit Works (KSM), totaling 33 people (Appendix 2). The sample used in this study was taken using the saturated sampling method, namely sampling where all members or elements of the population are used as opportunities. So the samples taken at PT. Karya Mandiri Spirit (KSM), which consists of 33 respondents. This research was conducted at PT. Karya Mandiri Spirit (KSM) which is located at Jl. Karang Sari, Sukasari, Kec. Pegajahan, Serdang Bedagai Regency, North Sumatra, 20986. Data collection techniques used to obtain data or information, Observation, Documentation, Questionnaire Based on the research results table it can be seen that the Fcount value is 61,661 with a Ftable value of 2.66 where the Fcount value is greater than Ftable, namely 61,661. besides that it can also be seen that the value of sig. of 0.000 where the value of sig. smaller than 0.05 or 0.000 <0.05, then in this case Ho is rejected and Ha is accepted, meaning that performance expectations (X1), business expectations (X2), social factors (X3), and facilitating conditions (X4) are significant to interest in the use of accounting information systems (Y).